A Young Women with Infected Polycystic Lung Disease That Affects the Quality of Life - Suwandi, Gede Sasmika; Djajalaksana, Susanthy (Malang Respiratory Journal, 2021)
Introduction: Polycystic lung disease (PLD) is a group of diseases with heterogeneous pathophysiological processes. The demographics and clinical symptoms vary widely. The etiology of PLD is related to neoplasms, genetics, lymphoproliferative disorders, infections, interstitial diseases, smoking, and developmental disorders. In HRCT, cystic, nodular, ground glass opacities and pneumothorax can be found. Tissue biopsy and immunohistochemistry are needed to determine the type of PLD. Age is very influential towards the survival rates, rapid decline in lung function often occurs at a young age, thus, causing long-term complications in the cardiovascular systemCase Description: A 14-years-old woman complained of shortness of breath and cough was diagnosed with Poly cystic lung disease with Lung TB as secondary infection. CT Scan Thorax showed multiple cavities with consolidation, abdominal ultrasound of the ovary found a simple cystic lesion. The patient underwent TB treatment. After evaluation, clinical symptoms improved, but the patient is often absent from school, thus, indicating disruption in quality of life. Spirometry data showed decreased pulmonary function ad modum restriction, and moderate obstruction. The patient is planned to undergo several examinations such as Bodypletysmography, Bronchoscopy, and VATS to obtain tissue samples, so a diagnosis can be made. Considering the age of the patient—who is still young—definitive therapy as a continuation is expected to improve the patient's quality of life.Conclusion: The diagnosis of PLD in the patient still requires further examination. Other tests, such as biopsy followed by immunohistochemical examination, can be used to confirm the type of PLD. Currently, the patient is undergoing TB treatment and routine control to the clinic. Ater treatment, the clinical symptoms alleviated, but shortness of breath is still present, especially felt after walking fast and carrying heavy loads. Spirometry was done as an evaluation of pulmonary function, showing moderate restriction and obstruction. It is clear that PLD affects the quality of life in this patient.